A Discontinuous Galerkin Method by Patch Reconstruction for Biharmonic Problem (Journal of Computational Mathematics, 2019)
We propose a new discontinuous Galerkin method based on the least-squares patchreconstruction for the biharmonic problem. We prove the optimal error estimate of theproposed method. The two-dimensional and three-dimensional numerical examples arepresented to confirm the accuracy and efficiency of the method with several boundaryconditions and several types of polygon meshes and polyhedral meshes.